HUBUNGAN STROKE SELF MANAGEMENT DENGAN KUALITAS HIDUP PASIEN STROKE - Mufidah, Nisfil; Wahyudi, Rahmad; Zamilah, Zamilah (NHM PRESS, 2025)
Stroke is a disorder of brain function that occurs suddenly. Preliminary studies show low quality of life in stroke patients in the work area of ANNA Medika Madura General Hospital. The purpose of the study is to analyze the relationship between stroke Self-Management with the quality of life of post-stroke patients in the work area of ANNA Medika Madura General Hospital. The research design used Analytic Correlative with Cross Sectiona approach. The study population was 35 stroke patients in the working area of ANNA Medika Madura General Hospital. The research sample of 32 respondents was selected using a simple random sampling technique. The Independent variable were stroke Self-Management and the dependent variable was quality of life. The research instrument used a Stroke Self-Management Questionnaire (SSMQ) and Quality Of Life Questionnaire (WHoqol-Breff). Test analysis using Spearman Rank statistical test. The results of the first Spearman Rank statistical test obtained p-value=0.000 means that there was a relationship between stroke self-management and the quality of life of post-stroke patients in the work area of ANNA Medika Madura General Hospital. Based on the results above, it is recommended that further researchers develop social support variables in post-stroke patients to be able to provide information to families to always increase motivation to always increase stroke self-management in post-stroke patients, in order to accept the reality of their quality of life.